Exploration of Parents' Perceptions of Nutrition Intervention Programs in Improving Early Childhood Cognitive and Social Development: A Case Study at an Early Childhood Institution - Arifin, Zainul; Zainuddin, Mohammad; Arifin, Imron; Hayatiningsih, Ula Nur; Aisyah, Eny Nur (JURNAL PENDIDIKAN USIA DINI, 2025)
This study aims to explore parents' perceptions of nutrition intervention programs in supporting the cognitive and social development of early childhood at the An Nur Early Childhood Education Institution in Malang Regency. This study uses a qualitative approach with a case study design and involves 10 parents selected through purposive sampling based on their level of active participation in the program and diversity of backgrounds. Data were collected through semi-structured in-depth interviews, direct observation of daily PAUD activities, and program documentation. Analysis was conducted using thematic analysis techniques to identify patterns and main themes. The results of the study indicate that parents perceive various benefits from the nutrition intervention program, including improved immune system, learning concentration, and children's social skills such as sharing and empathy. However, challenges remain, particularly in maintaining healthy eating patterns at home. Parents also suggested nutrition training, cooking activities, and regular health check-ups as forms of ongoing support. This study emphasizes the importance of a collaborative approach between parents, teachers, and institutions in the success of nutrition intervention programs, and provides practical contributions for PAUD institutions seeking to adopt similar approaches.